Scalable ternary hierarchical microspheres composed of PANI/ rGO/CeO2 for high performance supercapacitor applications. (October 2019) - Jeyaranjan, Aadithya; Sakthivel, Tamil Selvan; Neal, Craig J.; Seal, Sudipta
Abstract: Designing hybrid conductive polymer structures that can effectively mitigate capacitance fade and improve cycle life is critical to developing viable conductive polymer-based supercapacitors. Low cost and high yield synthesis methods that can be easily scaled-up are also crucial for industry-scale production. Herein, we report a highly scalable porous hierarchical microspheres composed of polyaniline nanofibers (PANI), reduced graphene oxide (rGO), and cerium oxide nanorods (CNRs) synthesized through a spray drying method. The functional and structural synergistic effect of the three components assembled as a 3D porous hierarchical structure which maximizes ion and charge transport while mitigating restacking and agglomeration of the nanostructures results in a composite supercapacitor material with superior electrochemical properties. The optimized ternary hierarchical microspheres exhibit a high specific capacitance (684 F g −1 ), good rate capability, excellent cycle life (92% capacitance retention after 6000 cycles at 4 A g −1 ). Furthermore, an asymmetric device fabricated with the ternary composite exhibits a high specific energy density (46.27 W h kg −1 ) at a power density of 850 W kg −1 with a very stable cyclic performance and high coulombic efficiency. Thus, we demonstrate, for the first time, a highly scalable method to produce PANI/rGO/CNR based hierarchical microspheres as high-performance supercapacitor material. Graphical abstract: Outstanding electrochemical properties can be achieved through the structural and functional synergy of the unique multi-component porous hierarchical microspheres.Image 1